2023
DOI: 10.1093/jas/skac288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of similar dietary roughage equivalency fed to beef steers during the growing and finishing phase

Abstract: The objective of this experiment was to determine the influence that similar dietary roughage equivalency offered in a single or two-diet system during a 210-d growing-finishing period has on growth performance, the efficiency of dietary net energy (NE) utilization, and carcass traits in beef steers. Beef steers (n = 46; initial shrunk [4%]; body weight [BW] = 281 ± 40.4 kg) were fed once daily, and bunks were managed according to a slick bunk management system across all 10 pens. Treatments included the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous work from our lab [1] demonstrated that a single growing-finishing diet achieved a similar outcome compared to a two-diet system. The results of the current experiment show that the larger and smaller tails of a population of cattle grew at similar rates with similar rates of accretion for both protein and fat.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previous work from our lab [1] demonstrated that a single growing-finishing diet achieved a similar outcome compared to a two-diet system. The results of the current experiment show that the larger and smaller tails of a population of cattle grew at similar rates with similar rates of accretion for both protein and fat.…”
Section: Discussionmentioning
confidence: 77%
“…and (5) managing feeder cattle supply into the feedlot phase of production. Previous work within our lab group conducted by Hamilton [1] demonstrates cattle fed a single growing-finishing diet had similar growth performance and carcass traits upon harvest at equal days on feed as compared to steers fed within a two-diet phase system. However, in that experiment we used steers that were uniform in weight.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Enhance the utilization of carbon from energy feeds to compete in an energy economy and improve national food security ( Acharya et al, 2023 ; Coulson et al, 2023 ; Francis et al, 2023 ; Hamilton et al, 2023 ; Larson et al, 2023a and b ; Tarnonsky et al, 2023a and b ; Troyer et al, 2023 ; Wilson et al, 2023 ; Winders et al, 2023 ).…”
mentioning
confidence: 99%